Calycosiphonia or Kupeantha (Coffeeae, Rubiaceae)? A morphological and molecular study of a new species from the Albertine Rift - Ntore, Salvator; Nkengurutse, Jacques; de Backer, Sander; Sonké, Bonaventure; De Block, Petra; Janssens, Steven B.; Verstraete, Brecht; Robbrecht, Elmar (European Journal of Taxonomy, 2024)
Field work in the Kibira National Park (Burundi), located in the Kivu-Ruwenzori system of the Afromontane Region, revealed the existence of a new species clearly belonging to the Argocoffeopsis-Calycosiphonia clade (Coffeeae, Rubiaceae). The species shows striking heterophylly: the plagiotropous branches have several nodes bearing reduced or even scaly leaves. For the rest, it shares characters with Calycosiphonia and Kupeantha. Therefore, a morphological comparison with the clade is done, as well as molecular phylogenetic analyses. The morphology of the novelty is closer to Kupeantha than to Calycosiphonia, inter alia because the anthers have no transverse septa, in contrast to the multilocellate anthers of Calycosiphonia. However, the molecular data advocate for a position in Calycosiphonia – a result weakening the morphological distinction between Calycosiphonia and Kupeantha. The former genus is no longer restricted to species with transverse septa in the anthers and with placental outgrowths around the seed. The new species is formally described as Calycosiphonia albertina Ntore & Robbr. sp. nov. Nomenclaturally, this placement is also the most conservative option. A taxonomic treatment, illustrations, a geographical distribution map, and a preliminary conservation assessment are provided. The previous inclusion of Calycosiphonia pentamera in Kupeantha based on morphology is here corroborated by molecular analyses.